The role of plate movements on reservoir development of the Iranian carbonate formations: A review of the interplay between tectonics, paleoclimate, and diagenesis - Vahid Tavakoli; Hosein Barfizadeh (Results in Earth Sciences)
This article reviews and assesses the reservoir characteristics of several geologic Formations in the northeast of the Arabian plate, from the Permian–Triassic to Oligo-Miocene, and evaluates the complex interrelations between tectonic activities, paleoclimatic conditions and diagenetic alterations. All of these Formations have been deposited in a ramp depositional setting. Both dolomitization and dissolution diagenetic processes have significantly enhanced the reservoir quality by altering the porosity and permeability of the Permian–Triassic Kangan and the Dalan Formations. The diagenetic processes of dissolution, fracturing, and localized dolomitization have enhanced the reservoir properties of the Fahliyan Formation's carbonate sequence. The Cretaceous Dariyan exhibits a gradual facies transition where dissolution enhances reservoir quality, while cementation and compaction diminish reservoir properties. For the mid-Cretaceous Sarvak Formation, the investigation addressed the diagenetic history triggering the creation of secondary porosity, related to meteoric processes and karstification. Finally, the Oligo-Miocene Asmari Formation is presented as a major hydrocarbon reservoir with extensive carbonate facies. Tectonic-driven fracturing and faulting increased reservoir quality by altering primary porosity and permeability and inducing significant diagenetic changes within a complex biodiverse reef ecosystem. This paper aims to comprehensively review and analyze the interaction between facies, diagenesis, tectonic activities, and paleoclimate across several geological Formations in the study area. By synthesizing existing literature and conducting a comparative analysis, the study seeks to elucidate how these factors collectively influence reservoir properties and dynamics. This approach not only identifies current knowledge gaps but also provides insights into potential avenues for future research and scientific exploration.